Creating intoxigenic environments: Marketing alcohol to young people in Aotearoa New Zealand - McCreanor, Tim; Moewaka Barnes, Helen; Kaiwai, Hector; Borell, Suaree; Gregory, Amanda (Elsevier, 2008)
Alcohol consumption among young people in New Zealand is on the rise. Given the broad array of acute and chronic harms that arise from this trend, it is a major cause for alarm and it is imperative that we improve our knowledge of key drivers of youth drinking. Changes wrought by the neoliberal political climate of deregulation that characterised the last two decades in many countries including Aotearoa New Zealand have transformed the availability of alcohol to young people. Commercial development of youth alcohol markets has seen the emergence of new environments, cultures and practices around drinking and intoxication but the ways in which these changes are interpreted and taken up is not well understood. This paper reports findings from a qualitative research project investigating the meaning-making practices of young people in New Zealand in response to alcohol marketing. Research data included group interviews with a range of Maori and Pakeha young people at three time periods. Thematic analyses of the youth data on usages of marketing materials indicate naturalisation of tropes of alcohol intoxication. We show how marketing is used and enjoyed in youth discourses creating and maintaining what we refer to as intoxigenic social environments. The implications are considered in light of the growing exposure of young people to alcohol marketing in a discussion of strategies to manage and mitigate its impacts on behaviour and consumption.
Keywords: Marketing; Alcohol; Youth; Intoxication; Policy; New Zealand; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321299 Public health and health services not elsewhere classified